Transformation of Journalistic Work Culture in the Era Media Convergence at Palangka Post and Infokalteng in Palangka Raya City - Ahmad Anshari; Usup Riassy Christa; Roby Sambung; Vivy Kristinae (JURNAL ECONOMINA, 2026)
Media convergence has fundamentally transformed journalistic work by reshaping organizational culture, job design, work demands, and human resource management practices. This study aims to analyze the transformation of journalistic work culture within media organizations implementing media convergence by employing the Human Resource Management perspective through the concepts of work redesign and the Job Demands–Resources (JD-R) Model. A qualitative approach with a multiple case study design was employed in two local media organizations in Palangka Raya, namely SKH Palangka Post and Infokalteng. Data were collected through in-depth interviews with eight informants, non-participant observation, document analysis, and were analyzed using NVivo through open coding, axial coding, and selective coding. The findings reveal that media convergence has transformed organizational work culture, redesigned journalistic jobs into multi-platform practices, increased job demands through tighter deadlines, multitasking, and work intensification, while simultaneously requiring organizations to provide adequate job resources, including editorial support, newsroom coordination, digital competency development, and technological facilities. The study concludes that successful transformation of journalistic work culture depends not only on technological adoption but also on maintaining a balance between job demands and job resources to sustain journalistic quality. These findings strengthen the contribution of Human Resource Management perspectives in explaining work culture transformation within media organizations in the era of media convergence.